MIGRATION IN WEST AFRICA: AN ANALYSIS OF PULL AND PUSH FACTORS - OLUWAGBENGA EMMANUEL ADEBAYO; MARY MOMSISURI BOTESO (International Studies Journal)
The purpose of this paper is to analyze the factors that influence net migration in West Africa. Panel data on variables like net migration, wage rate, and unemployment in four selected West African countries (Nigeria, Ghana, Sierra Leonne and Senegal), spanning a period of twenty-five years (1997-2021) were collected from secondary sources like the World Bank, and analyzed using the fixed effects model with cluster- robust standard errors. The results of the study revealed that GDP per capita has a negative but non-significant effect on net migration (p > 0.05). Wage rate has a positive but non-significant effect on net migration (p > 0.05). The effect of unemployment on net migration is negative and statistically significant (p < 0.05). The study recommends that the government and policy makers should create more jobs and also increase wages in other to discourage emigration and to attract human capital into the affected countries, thereby increasing net migration. The work is original because unlike most studies that were country-specific, this study made use of panel data collected on four African countries (Nigeria, Ghana, Sierra-Leone and Senegal). The study also employed the fixed effects model with cluster robust standard errors.